The detection of episodic memory in others biases social choice - Elisa Ciaramelli; Anna Waisman; Debora Stendardi; Morris Moscovitch (Proceedings of the National Academy of Sciences, 2026)
We often share personal memories with others, but the social function of episodic memory retrieval is not clear. In two experiments (N 1 = 50, N 2 = 125), run in two different labs, in different countries with different languages, and using naturalistic as well as experimentally crafted personal narratives, we show that participants can distinguish between context-rich (episodic) memories and context-poor (semantic) memories shared by others, and consistently ascribe greater memory ability to individuals sharing episodic compared to semantic personal memories. Moreover, participants report stronger social preference and feelings of closeness for individuals sharing personal episodic memories. The appraisal of episodic quality in memories shared by others, and not inferred personality traits of the narrator, predicted interpersonal closeness on a trial-by-trial basis. These findings reveal a fundamental social function of the episodic memory system: enabling the sharing of context-rich personal memories that foster close relationships. We propose that preferring partners who display strong episodic recall may confer adaptive advantages, linking social selection to the effectiveness of memory systems, particularly hippocampal function.